2009
DOI: 10.1523/jneurosci.6026-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Theataxia3Mutation in the N-Terminal Cytoplasmic Domain of Sodium Channel Nav1.6 Disrupts Intracellular Trafficking

Abstract: The ENU-induced neurological mutant ataxia3 was mapped to distal mouse chromosome 15. Sequencing of the positional candidate gene Scn8a encoding the sodium channel Na v 1.6 identified a TϾC transition in exon 1 resulting in the amino acid substitution p.S21P near the N terminus of the channel. The cytoplasmic N-terminal region is evolutionarily conserved but its function has not been well characterized. ataxia3 homozygotes exhibit a severe disorder that includes ataxia, tremor, and juvenile lethality. Unlike S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 55 publications
(82 reference statements)
1
59
0
Order By: Relevance
“…6. It has been reported that the cytoplasmic N-terminal domain of Nav1.6 is required for anterograde transport from the Golgi complex to the plasma membrane (53) and that the microtubule-associated protein MAP1B interacts with Nav1.6 and facilitates its trafficking to the cell surface (54). It remains to be elucidated whether APP enhances the surface expression of Nav1.6 by promoting forward trafficking or by decreasing the endocytosis of sodium channels from the cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…6. It has been reported that the cytoplasmic N-terminal domain of Nav1.6 is required for anterograde transport from the Golgi complex to the plasma membrane (53) and that the microtubule-associated protein MAP1B interacts with Nav1.6 and facilitates its trafficking to the cell surface (54). It remains to be elucidated whether APP enhances the surface expression of Nav1.6 by promoting forward trafficking or by decreasing the endocytosis of sodium channels from the cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…The c.667A>G nucleotide mutation was introduced into the tetrodotoxin (TTX)-resistant derivative of the murine Nav1.6 cDNA clone Nav1.6 R as previously described (Sharkey et al, 2009). Mouse Scn8a is an appropriate model for human SCN8A , since the human and mouse proteins are 99% identical in amino acid sequence (Plummer et al, 1998), and in vivo expression of the human epileptic encephalopathy mutation N1768D in the mouse results in a similar phenotype of early onset convulsive seizures and SUDEP (Jones and Meisler, 2014)(and unpublished observations by MHM).…”
Section: Methodsmentioning
confidence: 99%
“…Channel activity was evaluated by co-transfection of the eGFP cDNA together with mutant or wildtype Nav1.6 murine cDNAs into the dorsal root ganglion (DRG) neuron-derived cell line ND7/23 as previously described (Sharkey et al, 2009; Veeramah et al, 2012). ND7/23 neuronal cells support larger Nav1.6 currents than HEK293 cells, and have been our preferred expression system for voltage-clamp experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Four spontaneous mutations of Scn8a channels in mice have been reported (Table 1) [16][17][18][19][20][21][22]). Scn8a med and Scn8a medTg are two null mutations with clinical signs of paralysis, muscle atrophy, and failure of neuromuscular transmission; such mice live for only 21-24 days.…”
Section: Scn8a Channel Mutationmentioning
confidence: 99%
“…Scn8a ataxia3 has an induced mutation that produces a phenotype resembling those of the null mutations except that partial hindlimb function is retained. Retention of the Na v 1.6 channel protein in the Golgi complex prevents its adequate transport to the cell membrane [21].…”
Section: Scn8a Channel Mutationmentioning
confidence: 99%